2016
DOI: 10.1080/1828051x.2016.1221747
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effectiveness of an innovative semen extender (Formula®) comparing with a traditional extender (Lepus®) for artificial insemination in rabbits does

Abstract: This study aimed to investigate the preservability and viability of the rabbit spermatozoa diluted in a new semen extender Formula V R in comparison with Lepus V R at 17 C of storage. The main characteristic of the new extender formulation is the use of an enzymatic agent associated to a polysaccharide as energy source precursor, added with gentamycin. During eight trials, ejaculates from 70 bucks were collected and diluted at 1:10 ratio with both the extenders, after 24 h of storage the semen doses were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
2
2
0
2
Order By: Relevance
“…Our results show that among the selected biomolecules, GEN proved to be the best motion-preserving supplement. A similar observation was reported by Bresciani et al [18] who developed a new extender for rabbit semen containing up to 40 mg/mL GEN. Nevertheless, we have to treat our results with caution as Jasko et al [54] emphasized on the harmful effects of GEN on the motility of stallion spermatozoa at concentrations greater than 1 mg/mL.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our results show that among the selected biomolecules, GEN proved to be the best motion-preserving supplement. A similar observation was reported by Bresciani et al [18] who developed a new extender for rabbit semen containing up to 40 mg/mL GEN. Nevertheless, we have to treat our results with caution as Jasko et al [54] emphasized on the harmful effects of GEN on the motility of stallion spermatozoa at concentrations greater than 1 mg/mL.…”
Section: Discussionsupporting
confidence: 86%
“…The microbiological assessment of the control and experimental samples revealed that all ATBs performed better against the growth of E. faecalis in comparison with the selected natural biomolecules. As expected, and indeed indicated in previous reports, GEN and KAN are considered to be antibacterial substances of choice for semen extenders in rabbits [18,19], stallions [86] and bulls [87]. Nevertheless, the ever-increasing bacterial tolerance and/or resistance towards antibiotics needs to be remembered.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Первая среда содержит следующие компоненты: трис(гидроксиметил)аминометан -3,029 г, лимонная кислота -1,676 г, дегидрированная D-глюкоза -1,25 г, стрептомицин -75000 IU, G-пенициллин -166200 IU, вода дистиллированная -до 100 мл; pH -7,14; осмоляльность -299 мОсм/кг. В состав второй среды входят: хлорид натрия -5,690 г, хлорид калия -0,231 г, хлорид кальция 2-водный -0,294, магния хлорид 6-водный -0,081г, натрий фосфорнокислый двузамещенный (гидрофосфат натрия) -0,040 г, натрия гидрокарбонат -2,090 г, натрия пируват -0,022 г, D-глюкоза -0,900 г, молочная кислота -3,680 г, HEPES (4-(2-гидроксиэтил)-1-пиперазин этансульфоновая кислота -буферный агент) -2,380 г стрептомицин -75,000 IU, G-пенициллин -166,200 IU, вода дистиллированная -до 1 л; pH -7,40; осмоляльность -296 мОсм/кг [12,14,15].…”
Section: разведение селекция генетикаunclassified